Neuroborreliosis in a horse with common variable immunodeficiency. (March 2019) - Pecoraro, Heidi L.; Felippe, M. Julia B.; Miller, Andrew D.; Divers, Thomas J.; Simpson, Kenneth W.; Guyer, Kimberly M.; Duhamel, Gerald E.
Common variable immunodeficiency (CVID) is a rare condition in adult horses characterized by hypogammaglobulinemia and increased susceptibility to parasitic and bacterial infections, including recurrent respiratory diseases, septicemia, and meningitis. Lyme disease is often included as a differential diagnosis in CVID horses with signs of meningitis; however, the Borrelia burgdorferi organism has not been demonstrated previously within central nervous system tissues of CVID horses with neurologic disease, to our knowledge. We report herein a case of neuroborreliosis in a CVID horse, confirmed by combined immunologic testing, histopathology, real-time PCR assay, fluorescent in situ hybridization, and immunohistochemical staining. Implications of these findings include heightened monitoring of CVID horses for Lyme disease in endemic areas and appropriate therapy in the case of neurologic disease.